2010
DOI: 10.1021/cb100219n
|View full text |Cite
|
Sign up to set email alerts
|

A Novel and Specific NADPH Oxidase-1 (Nox1) Small-Molecule Inhibitor Blocks the Formation of Functional Invadopodia in Human Colon Cancer Cells

Abstract: The NADPH oxidase (Nox) proteins catalyze the regulated formation of reactive oxygen species (ROS) which play key roles as signaling molecules in several physiological and pathophysiological processes. ROS generation by the Nox1 member of the Nox family is necessary for the formation of extracellular matrix (ECM)-degrading, actin-rich cellular structures known as invadopodia. Selective inhibition of Nox isoforms can provide reversible, mechanistic insights into these cellular processes in contrast to scavengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
154
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(158 citation statements)
references
References 40 publications
4
154
0
Order By: Relevance
“…APO is one of the most frequently used NOX inhibitors and may also act as an antioxidant (13). However, because of the lack of specificity of DPI and APO, novel and more selective NOX inhibitors, such as VAS, VAS3947, and 2-acetylphenothiazine (2APT), have been developed (9,35,40). Because these NOX inhibitors have been used in numerous physiological, cell biological, and biochemical studies, knowing the effects of these compounds on targets unrelated to NOX can be quite helpful and informative.…”
mentioning
confidence: 99%
“…APO is one of the most frequently used NOX inhibitors and may also act as an antioxidant (13). However, because of the lack of specificity of DPI and APO, novel and more selective NOX inhibitors, such as VAS, VAS3947, and 2-acetylphenothiazine (2APT), have been developed (9,35,40). Because these NOX inhibitors have been used in numerous physiological, cell biological, and biochemical studies, knowing the effects of these compounds on targets unrelated to NOX can be quite helpful and informative.…”
mentioning
confidence: 99%
“…Expression of Nox1 seems to be relatively high in colon epithelial cells than that in other normal cell types (19). In colon cancer cells, the known function of Nox1 is conflicting: one study suggested that Nox1 was downstream of 12-HETE and was responsible for cell proliferation but not for cell spreading (20); another study suggested that Nox1 was responsible for cell invasion (6). In this study, we inves-…”
Section: Introductionmentioning
confidence: 91%
“…To answer this question, we performed immunohistochemistry using Nox1-specific antibody on tissue arrays, which includes normal and cancer tissues Grades 1 to 3, Stages I -IV, and various TNM stages (Table 1) Nox1 levels are higher in primary SW480 than that in metastatic SW620 cells Because ROS plays a key role in cell motility and invasion (21), inhibition of Nox1 was previously shown to inhibit invadopodia formation in colon cancer cells (6). We next examined Nox1 expression levels in SW480 and SW620 cells.…”
Section: Nox1 Level Is Not Associated With Colon Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the available Nox inhibitors, there is much difference in opinion with regard to the most specific and efficient, and the choice is also limited by suitability to a particular cell type as well as the nature of the downstream effect of interest. Some compounds branded as Nox inhibitors, appear to function more preferentially as an anti-oxidant or free-radical scavenger (Heumuller et al, 2008), 2006), GKT136901 (Page P et al, 2008), ML171 (Gianni et al, 2010), ebselen and its analogs (Smith et al, 2012). It is possible that one or several of these, will be shown to demonstrate definitive, specific Nox inhibition.…”
Section: Quantitative Reverse Transcriptase Polymerase Chain Reactionmentioning
confidence: 99%